Ultrasmall superparamagnetic Ni nanoparticles embedded in polyaniline as a lightweight and thin microwave absorber. Issue 82 (5th September 2015) - Han, Dandan; Xiao, Ningru; Hu, He; Liu, Bao; Song, Gengxin; Yan, He
<x xml:space="preserve">Abstract</x> In this work, we have reported the preparation and lightweight and thin microwave absorbent application of ultrasmall Ni nanoparticles embedded in polyaniline (PANI).